Innovation engineering as the instrument of decision-making support - Kraskevich, V.E.; Selivanova, A.V. (Математичне моделювання в економіці, 2017)
The proposed methods of assessment of the innovation project by way of application of innovation engineering as the information-analytical instrument. Methodology of situation modeling has been used for assessment of the innovation project technological decisions effectiveness. Запропоновано метод оцінки інноваційного проекту на основі інноваційного інжинірингу як інформаційно-аналітичного інструменту. Застосування методології ситуаційного моделювання для оцінки ефективності технологічних рішень інноваційного проекту. Предложен метод оценки инновационного проекта на основе инновационного инжиниринга как информационно-аналитического инструмента. Применение методологии ситуационного моделирования для оценки эффективности технологических решений инновационного проекта.